DESIGN, PREPARATION, AND IN SILICO STUDY OF NOVEL CURCUMIN-BIPHENYL CARBONITRILE CONJUGATE AS NOVEL ANTICANCER DRUG MOLECULES - KRISHNAMURTHY, GEETA; DEEPTI ROY, LAIRIKYENGBAM; KUMAR, JYOTSNA; PRABU, N MANIKANDA; GOUR, POOJA; ARLAND, SHIVANJALI ESTHER (International Journal of Applied Pharmaceutics, 2023)
Objective: To design and synthesize the novel curcumin derivatives of curcumin-biphenyl carbonitrile conjugate to study their ADMET, drug-like behaviour and cytotoxicity on PANC1 cell lines. Methods: Binding affinity of designed novel Curcumin analogues were assessed by molecular docking against the target protein (KRAS). Structures of lately synthesized compounds were characterized by spectral analysis. ADMET (absorption, distribution, metabolism, excretion, and toxicity) drug-likenesses behaviour prediction of synthesized curcumin analogues was done by computational analysis. The stability of the synthesized curcumin analogues was carried out by force degradation method as per ICH guidelines. In vitro cytotoxic assessment of these novel compounds on PANC 1 cancer cell lines was assessed by MTT assay. Results: Three hit molecules were identified, which had the best binding affinity against the target protein KRAS having a docking score of -7.21 for CD2,-7.05 for CD3, and-6.80 for CD1. Most of the Pharmacokinetic (ADME) parameters are found to be quite agreeable and in the satisfactory range. 1H-NMR, FTIR and Mass spectrographic methods confirmed the structures. All three synthesized novel curcumin analogues were stable for a period of three months. Results of anti-proliferative activities indicated their cogent anticancer activity against PANC 1 cell line (IC50 = 67.51 μM@CD1, 45.27 μM @CD2 and 168.60 µg/ml @CD3). Conclusion: This study demonstrated that curcumin-biphenylcarbonitrile conjugate could be used as a plausible pharmacophore for targeting KRAS protein and will be supportive to explore the new series of cogent curcumin derivatives as anticancer agents.